Anti-Ro60 Seropositivity Determines Anti-Ro52 Epitope Mapping in Patients With Systemic Sclerosis - Gkoutzourelas, Athanasios; Liaskos, Christos; Mytilinaiou, Maria G.; Simopoulou, Theodora; Katsiari, Christina; Tsirogianni, Alexandra; Daoussis, Dimitrios; Scheper, Thomas; Meyer, Wolfgang; Bogdanos, Dimitrios P.; Sakkas, Lazaros I. (Frontiers in Immunology, 2018)
Epitope mapping of anti-Ro52 antibodies (Abs) has been extensively studied in patients with Sjögren’s syndrome (SjS) and systemic lupus erythematosus (SLE). Comprehensive epitope mapping in systemic sclerosis (SSc), where anti-Ro52 antibodies are also frequently detected, has not been performed. The aim of the present study was to fully characterize Ro52 epitopes in anti-Ro52-positive SSc using Ro52 fragments spanning the full antigen. Further analysis was made according to anti-Ro60 status. Epitope mapping was performed in 43 anti-Ro52-positive SSc patients. Seventy eight anti-Ro52-positive pathological controls, including 20 patients with SjS, 28 patients with SLE, 15 patients with dermatomyositis (DM) and 15 patients with primary biliary cholangitis (PBC), and 20 anti-Ro52-negative healthy individuals as normal controls were also tested. Five recombinant Ro52 fragments [Ro52-1 (aa 1-127), Ro52-2 (aa 125-268), Ro52-3 (aa 268-475), Ro52-4 (aa 57-180), and Ro52-5 (aa 181-320) were used to test reactivity by line-immunoassay and in house ELISA. Anti-Ro60 reactivity was tested by ELISA. All anti-Ro52 positive sera reacted with Ro52-2; none recognized Ro52-3. Antibodies against Ro52-1 were less frequently found in SSc than in SjS/SLE (11.6% vs 41.7%, p=0.001); and antibodies against Ro52-4 were less frequently found in SSc than in SjS/SLE (27.9% vs 50%, p=0.03). In SSc patients, reactivity against Ro52-1 was more frequent in anti-Ro52+/anti-Ro60+ than in anti-Ro52+/anti-Ro60-patients (33.3% vs 0%, p=0.003). In this comprehensive analysis of Ro52 epitope mapping in SSc, the coiled coil domain remains the predominant epitope on Ro52. Contrary to SjS and SLE, patients with SSc fail to identify epitopic regions within the N-terminus of the protein, especially if they lack con-current anti-Ro60 reactivity.